Paediatric Orthopaedics An Evidence-Based Approach to Clinical Questions - Alshryda, Sattar; Huntley, James S.; Banaszkiewicz, Paul A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a refined clinical guide for evidence-based recommendations in paediatric orthopaedics. Focusing on specific body regions (hip, knees, ankle and feet, spine, shoulder, elbow and wrist and hand) this resource addresses clinical questions related to conditions in these areas. A background section in each chapter sets the scene for the best available practice and also appraises the evidence for its strength and weakness. At the end of each chapter, the authors$1 (Bprovide recommendations on future research. Paediatric Orthopaedics: An Evidence-Based Approach to Clinical Questions has been edited by a team of surgeons with a great interest in evidence-based practice, who have brought together a group of international experts to produce this timely book. A wide spectrum audience including paediatric orthopaedic surgeons, trauma surgeons, orthopaedic residents, emergency department doctors, general practitioners and medical students looking for an evidence based approach to paediatric orthopaedics will find this book to be an essential guide for clinical practice.s
Part 1 General Guidance -- An Introduction to Evidence-Based Orthopaedics -- How to Read a Paper -- Part 2 Core structured topics -- The Hip -- The Knee -- The Foot and ankle -- The Spine -- The Shoulder -- The Elbow -- The Hand and Wrist -- Neuromuscular diseases -- Musculoskeletal infections -- Musculoskeletal tumours -- Skeletal Dysplasia -- Metabolic Bone Diseases -- Physis and Leg Deformity -- Miscellaneous paediatric conditions. .
Keywords: Medicine; Orthopedics; Pediatrics; Medicine & Public Health; Orthopedics; Pediatrics